EXPLORING THE DIGITAL CULTURAL DIVIDE: THE USE OF DIGITAL TECHNOLOGIES - Wahyudi, Agus; Syaiful, Yuanita (DIVERSITY Logic Journal Multidisciplinary, 2023)
BackgroundThe phenomenon of the spread of the Corona Virus Disease (COVID-19) in various parts of the world has implications for all aspects of life, one of which is education and learning. The demands of digital-based adaptive learning as the demands of the world of education must meet these demands. Van Dijk's digital divide theory is an instrument to observe the phenomena that occur, as well as Everet M. Rogers' perspective with Adoption Diffusion Theory (ADT) as a treatment for campus teaching programs that bridge the digital culture gap.Research PurposeThe research purpose was to lead the emergence of digital cultural imbalances for teachers in accessing e-learning at Al Mufidah Elementary School, Surabaya. Research MethodThis study uses a qualitative approach through in-depth interviews with 13 teachers at the research location with a total sampling method to map the digital culture gap like what happened in the research locationFindingsThe results of this study are the differences in resources experienced by teachers have an impact on the duration of access (often using the default application but never used for learning), mental, and social (teachers become passive).ConclusionThe most dominant access differences are differences in motivation (teachers do not have strong motivation to access), materials (teachers do not have sufficient competence to access technology and digital learning platforms every day), skills and use (teachers are not intense in using digital technology, do not using applications while learning).